Axial Uplift Behaviour of Belled Piers in Coarse-Grained Saline Soils. (4th November 2018) - Xu, Jian; Ren, Jianwei; Wang, Songhe; Jin, Long; Yuan, Jun
Abstract : Bearing capacity of belled pier foundation is critical in designing transmission lines in coarse saline soil region. This paper describes model test results on belled pier foundations. Axial uplift behaviours including failure modes, load-displacement curves, and ultimate uplift bearing capacity were discussed. The failure planes in four cases were obtained from pulled out cone-shaped bodies. An empirical equation was developed with a critical parameter of an uplift angle in design. Results indicate the range where the ground uplift shows circular extension at higher loads and the overall shear failure finally occurred. The load-displacement curves are primarily softening, and the uplift bearing capacity for coarse-grained saline soils (CSS) in the crystalline state increases at larger thickness, higher than that in dissolved state. Failure planes all exhibit approximately linear change from bottom to up. The angles of uplift for soils in crystalline and dissolved states can be taken as 34° and 18°, while 32° for the conventional for the sake of safety. Uplift behaviour of belled piers in CSS was modelled incorporating a practical interface model, with both failure planes and plastic range.